Production of the cast pervious materials on basis of aluminium - A. A. Andrushevich; M. N. Churic; V. P. Kaptsevich; R. A. Kusin (Литьë и металлургия, 2003)
There are examined the peculiarities of the technology of production cast permeable materials and aluminium articles and alloys using washing out salt filters. There is studied the penetrability of the received materials.